Pelatihan Video Pembelajaran Menggunakan Aplikasi Filmora Premium Untuk Guru di Sekolah Dasar Pada Masa Pandemi - Abdul Azis; Gilang Aji Purnomo; Rahmania Nur Fadilah (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2022)
The learning process in schools during the current pandemic does not take place as usual due to the Covid19 virus that has hit the whole world including Indonesia, to overcome this problem Indonesia has implemented a policy (Lockdown) and does not allow people to gather in crowded places, SD Negeri 01 Dukuh waluh is one of the One elementary school located in the Banyumas area, precisely in Dukuhwaluh village, twin sub-district, Banyumas district, this school is the target of this service. Learning Video is a media that presents audio and visuals that contain good learning messages that contain concepts, principles, procedures, knowledge application theories to help understand a learning material. During the Pandemic. Teachers are leaders, parents and educators. Teachers at SDN N 1 Dukuhwaluh really want this kind of training, so that in delivering lessons to students it is not limited to Whatsapp Messenger, Filmora is one of the most popular video editing software that needs to be mastered if you want to try a career as a video editor. According to CompareCamp, one of the reasons that makes this software so popular is of course because of its various advanced features for editing video and audio. This application can be used to create and change videos according to the wishes of the school, and can be published to the internet media so that it can be known by elementary schools in the Banyumas Residency area. Based on the results of the research conducted, it is stated that the learning outcomes of students who use learning videos are higher than those of conventional learning. So it can be concluded that the use of learning videos in the online learning process can also improve student learning outcomes. The development of instructional video media that will be developed in schools is for classroom teachers. In addition, teachers will also be asked to try it themselves at home so they can make videos at home. In learning by using these learning videos, researchers will use a guided inquiry learning model to assist in conditioning teachers to learn virtually